1999
DOI: 10.1364/ol.24.001460
|View full text |Cite
|
Sign up to set email alerts
|

Grating resonances in air–silica microstructured optical fibers

Abstract: We report what is believed to be the first demonstration of optical fiber gratings written in photonic crystal fibers. The fiber consists of a germanium-doped photosensitive core surrounded by a hexagonal periodic air-hole lattice in a silica matrix. The spectra of these gratings allow for a detailed characterization of the fiber. In particular, the gratings facilitate coupling to higher-order leaky modes. We show that the spatial distribution and the effective index of these modes are determined largely by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
108
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(115 citation statements)
references
References 6 publications
4
108
1
2
Order By: Relevance
“…85 UVlaser exposure is a common technique for writing a FBG/ LPFG in a Ge-doped PCF with a photosensitivity. 12,86,87 In contrast, CO 2 laser irradiation is a highly efficient, low cost technique for writing a LPFG in a pure-silica PCF without photosensitivity. 20,24,25,27 Kakarantzas et al 20,88 reported, as shown in Fig.…”
Section: B To Write Lpfgs In Solid-core Pcfsmentioning
confidence: 99%
See 1 more Smart Citation
“…85 UVlaser exposure is a common technique for writing a FBG/ LPFG in a Ge-doped PCF with a photosensitivity. 12,86,87 In contrast, CO 2 laser irradiation is a highly efficient, low cost technique for writing a LPFG in a pure-silica PCF without photosensitivity. 20,24,25,27 Kakarantzas et al 20,88 reported, as shown in Fig.…”
Section: B To Write Lpfgs In Solid-core Pcfsmentioning
confidence: 99%
“…Periodic index modulations are usually required to realize mode coupling in in- fiber gratings. Although this presents no difficulties in conventional glass fibers, 16,21 solid-core PCFs, 12,20,25 and solid-core PBFs, 50,[94][95][96][97][98] it is very difficult, even impossible, to directly induce index modulations in an air-core PBF due to the air core structure, thereby seriously obstructing the development of PBF-based gratings over the past decade.…”
Section: To Write Lpfgs In Air-core Pbfsmentioning
confidence: 99%
“…In general, multiple microscopic air-holes lattice runs down longitudinally along the length of the optical fibre with different microstructure pattern. A novel waveguides property can be achieved by designing various air hole structures, size, shape and distribution of the holes, which may not be readily achieved in conventional optical fibres [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39] By doping the core of air-silica structured fibers with germanium, improved dispersion characteristics were achieved 40 showing larger customization. Germanium doping in the core allowed Bragg gratings to be written, 41 although some of the advantages of the structured fiber, particularly the evanescent field extending into the holes, are lost. Core cladding interactions also become problematic.…”
Section: Introductionmentioning
confidence: 99%